Racial and ethnic differences in health status and health behavior among breast cancer survivors—Behavioral Risk Factor Surveillance System, 2009 - White, Arica (J Cancer Surviv, 2012)
PURPOSE: Differences in health status and behavioral risk factors may explain racial/ethnic breast cancer disparities. We examined racial/ethnic differences in health status and behaviors among female breast cancer survivors compared to females without breast cancer. METHODS: Using cross-sectional data from the 2009 Behavioral Risk Factor Surveillance System, a national state-based, random sample telephone survey, we explored differences in self-rated health, obesity and selected behaviors (physical activity, smoking, alcohol use, fruit, and vegetable consumption) among females aged 18 years and older, who reported a previous breast cancer diagnosis (survivors, n=10,035) and those who reported no breast cancer history (n=234,375) by race/ethnicity. Adjusted prevalences of health status and behaviors, accounting for sociodemographics, comorbidities and health care access, were estimated by race/ethnicity. RESULTS: Compared to all other racial/ethnic groups, more white females reported heavy alcohol consumption and more black females reported obesity regardless of their breast cancer status. Among breast cancer survivors, more whites (33.7 %) were former smokers compared to blacks (24.5 %), “others” (20.5 %), and Hispanics (16.2 %) (p= 0.001). Racial/ethnic differences in obesity also varied by reported time since diagnosis (p value=0.018). Among long-term survivors (diagnosed ≥5 years before interview), more black survivors (34.8 %) reported obesity compared to white survivors (23.0 %). Also, among “other” race survivors, long-term survivors (22.0 %) reported more obesity than survivors diagnosed less than 5 years before interview (7.8 %). CONCLUSIONS: These findings suggest opportunities to increase health behaviors and reduce racial disparities among breast cancer survivors. IMPLICATIONS FOR CANCER SURVIVORS: Engaging in healthy behaviors can play a significant role in enhancing health outcomes and quality of life of breast cancer survivors. More research is needed to better understand racial differences in obesity, smoking and alcohol consumption in order to develop effective, culturally appropriate interventions to promote a healthy lifestyle after a breast cancer diagnosis.